ANALISIS PENGARUH HARI PERDAGANGAN TERHADAP RETURN SAHAM: PENGUJIAN WEEK-FOUR EFFECT DAN ROGALSKI EFFECT DI BURSA EFEK JAKARTA - Cahyaningdyah, Dwi (Journal of Indonesian Economy and Business, 2005)
The paper investigates the day of the week effect in Jakarta Stock Exchange by using 73active stocks during 2001-2003 period. The findings indicate that there is a day of the week effect in JSX. The highest and the lowest return are observed on Friday and Monday,respectively. Analysis of week-four effect in JSX find this phenomenon does not exist inJakarta Stock Exchange. This study shows that Monday effect occurs not only in the lasttwo weeks (fourth and fifth weeks) but also in the first three weeks.Investigation about relationship between Monday effect and Fridayâs return indicatesthat the negative mean return observed on Monday is not only the consequence of negative return occurring in earlier trading session. Futhermore, non-negative return on Friday also contributes to Monday effect. Further investigation shows that Rogalski effect presents in April. Finally, the study shows the Mondayâs return is only positive in April.Key words : Monday effect, week-four effect, Rogalski effect.